2019
DOI: 10.1038/s41598-019-39778-y
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate induces human hepatoma Hep3B cells apoptosis and necroptosis through inhibition of thioesterase domain of fatty acid synthase

Abstract: This study demonstrated that fenofibrate, a lipid-lowering drug, induced a significant time-dependent cytotoxicity of hepatoma Hep3B cells. Hep3B cells are significantly more sensitive to cell killing by fenofibrate than hepatoma HepG2, lung cancer CH27 and oral cancer HSC-3 cells. From the result of docking simulation, fenofibrate can bind excellently to the thioesterase domain of fatty acid synthase (FASN) binding site as orlistat, a FASN inhibitor, acts. The fenofibrate-induced cell cytotoxicity was protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 62 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…FASN is preferentially overexpressed in cancer cells and has been strongly linked to cancer cell proliferation and migration ( Jiang et al, 2012 ). Plenty of previous studies on cancer cells showed that inhibiting FASN can increase apoptosis ( Gonzalezguerrico et al, 2008 ; Richa et al, 2015 ; Sun et al, 2018 ; You et al, 2019 ). However, the demands of phGCs and hGCs for FASN are obviously lower than those of cancer cells, so the sensitivity of GCs to FASN inhibition may also be lower than that of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…FASN is preferentially overexpressed in cancer cells and has been strongly linked to cancer cell proliferation and migration ( Jiang et al, 2012 ). Plenty of previous studies on cancer cells showed that inhibiting FASN can increase apoptosis ( Gonzalezguerrico et al, 2008 ; Richa et al, 2015 ; Sun et al, 2018 ; You et al, 2019 ). However, the demands of phGCs and hGCs for FASN are obviously lower than those of cancer cells, so the sensitivity of GCs to FASN inhibition may also be lower than that of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…As shown, among diverse ginger phytochemicals (Fig S2 ), gingerenone family molecules had the highest affinity to the substrate binding site of the TE domain. Interestingly, the binding energies of these molecules were as low as fenofibrate, an experimentally-proved TE inhibitor 15 , and their binding energies were markedly lower than orlistat; which is another known TE inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…Since FASN thioesterase domain is involved in palmitate synthesis termination and also in maintaining of the length of fatty acid chain, it is particularly a promising target to inhibit the enzyme activity (TE dom). Orlistat and fenofibrate are the FASN inhibitors which can prevent tumor growth and induce malignant cell death through blocking the TE domain 15 . In order to predict the inhibitory effects of ginger phytochemicals on FASN activity, they were docked with the crystal structure of TE domain and their binding energies were compared to those of orlistat and fenofibrate, in order to prioritize these ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Fenofibrate has anticancer effects in a variety of cancers 35 , and it increases the sensitivity of tumors to chemotherapy and radiotherapy 36 , 37 . A literature review revealed that fenofibrate has anticancer effects in many malignancies, including pancreatic cancer 38 , lung adenocarcinoma 39 , hepatocellular carcinoma 40 , melanoma 41 , glioblastoma 42 , 43 , oral cancer 44 , 45 , prostate cancer 46 , 47 , breast cancer 48 , neuroblastoma 49 , and angiosarcomas 50 . Fenofibrate also increases the sensitivity of esophageal carcinoma 51 , 52 and head and neck squamous cell carcinoma 37 to radiotherapy, and that of breast cancer to chemotherapy 36 .…”
Section: Discussionmentioning
confidence: 99%